Lithuania and Lithuanians in Imants and Rimants Ziedonis’ Book Leišmalīte - Butkus, Vigmantas (Acta humanitarica academiae Saulensis, 2025)
The book of cultural journalism and essays, Leišmalīte (‘Latvian–Lithuanian Borderland’) (2012), by one of the most outstanding Latvian writers Imants Ziedonis (1933–2013) and his son Rimants Ziedonis (b. 1962) is dedicated to a specific Latvian region that lies at the border stretching for 600 km, named by a Latvian word leišmale (‘Latvian–Lithuanian borderland’). In Latvia, this word is much more frequently used and is more functional than its Lithuanian analogues meant to name the borderland on this side: “palatvijys”, “palatvė” (‘Lithuanian–Latvian borderland’).Inevitably, the book under analysis focuses on Lithuanians, Lithuania and diverse relationships between both ethno-linguistically kin nations of the Balts, i.e. both states. The article grounds on the classical principle of comparative literary imagology as a methodological approach to analyse an image of one country or its several elements reflected in literature, art, culture of another country. Referring to this principle, images of Lithuania and Lithuanians are explored in the book Palietuvėlė: both the images which are seen and assessed from the viewpoint of the Latvian–Lithuanian borderland region (leišmale), i.e. through the eyes of Latvian borderland inhabitants who became the “characters” of the book, and the images which are seen and assessed through the prism of the Latvian–Lithuanian borderland region, i.e. through the eyes of the authors of the book, the narrators.Attention is paid not only to the images but also to the story of their formation, functioning, dynamics of changes, their emotional or other kind of evaluation, their highly diverse contexts: historical, political, economic, commercial, cultural, administrative, even elementary domestic or criminal ones. The “communicating” variants are briefly characterised as specific instances: various situational and more stable connections of images based on the characteristic features of the Balts, their kin languages.The images of Lithuanians, Lithuania are being regularly formed in the book Palietuvėlė in the imagological manner based on comparison, when own, Latvian, realia are assessed at the background of analogous Lithuanian realia. Some stereotypical images of a Lithuanian person established in the historical-cultural memory of Latvians are being broken by substituting them with the images bearing an opposite meaning. In general, idealisation of the image of Lithuanians, Lithuania based on subjective experiences, personal imagination prevails in the book, even though there is also a mocking, critical point of view present.
Keywords: imagology; borderland literature; Latvian–Lithuanian borderland (Leišmalīte); image of Lithuanians and Lithuania